2007
DOI: 10.1002/cne.21318
|View full text |Cite
|
Sign up to set email alerts
|

Migration of sympathetic preganglionic neurons in the spinal cord is regulated by reelin‐dependent Dab1 tyrosine phosphorylation and CrkL

Abstract: The actions of Reelin in neuronal positioning in the developing cortex and cerebellum are relayed by Src-family kinase (SFK)-mediated phosphorylation of Dab1. Biochemical studies show that after phosphorylation Dab1 binds to an adaptor protein, CrkL. Whether CrkL is important for Reelin signaling in vivo is unknown, because crkl(-/-) embryos die before cortical development is complete. In the developing spinal cord, Reelin and components of its signaling pathway, VLDLR, ApoER2, and Dab1, control the positionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 52 publications
3
23
0
Order By: Relevance
“…CrkL -null embryos exhibit lethal defects in cardiac and neural crest development (Guris et al, 2001), precluding analysis of mature brain structures. However, there is a failure of preganglionic neuronal migration in the spinal cord mice lacking CrkL , but this defect is distinct from that seen in reeler (Yip et al, 2007). To analyze the tissue-specific contributions of Crk and CrkL to Reelin signaling, while avoiding the confounding effect of embryonic lethality, we generated floxed alleles for Crk and CrkL and crossed them with a Nestin-Cre transgene (Knoepfler et al, 2002) to obtain conditional mutations in Crk and CrkL in mouse neurons.…”
Section: Introductionmentioning
confidence: 81%
“…CrkL -null embryos exhibit lethal defects in cardiac and neural crest development (Guris et al, 2001), precluding analysis of mature brain structures. However, there is a failure of preganglionic neuronal migration in the spinal cord mice lacking CrkL , but this defect is distinct from that seen in reeler (Yip et al, 2007). To analyze the tissue-specific contributions of Crk and CrkL to Reelin signaling, while avoiding the confounding effect of embryonic lethality, we generated floxed alleles for Crk and CrkL and crossed them with a Nestin-Cre transgene (Knoepfler et al, 2002) to obtain conditional mutations in Crk and CrkL in mouse neurons.…”
Section: Introductionmentioning
confidence: 81%
“…It remains to be determined whether Crk and CrkL are required for neuronal positioning in the neocortex downstream of Dab1 tyrosine phosphorylation. The CrkL mutant has some similarities to Reeler-Dab1 phenotypes in the spinal cord, but not in the neocortex (Guris et al, 2001;Yip et al, 2007). The Crk-null animals die around E16 with cardiac and craniofacial defects precluding examination for a Reeler-like phenotype (Park et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These molecules are known to operate on a number of signaling pathways, making assessment of their role in reelin signaling more complex. A CrkL mutant has recently been shown to have a partial similarity to the Reeler phenotype in the spinal cord, but it does not have Reeler-like phenotypes in other areas of the CNS (Guris et al, 2001;Yip et al, 2007). This might be due to compensation by highly similar adaptor molecules encoded by the Crk gene: CrkI and CrkII.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that Reelin induced phosphorylation of n-cofilin at the leading processes and stabilized the actin cytoskeleton of migrating cortical neurons (Chai et al, 2009). Reelin-dependent SPN migration involves the lipoprotein receptors VldlR and ApoER2 and Dab1 tyrosine phosphorylation by SFK and CrkL (Yip et al, 2004(Yip et al, , 2007. CrkL has been shown to bind C3G, an exchange factor for the small GTPase Rap1 (Ballif et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Tissues were cryoprotected with 30% phosphate-buffered sucrose and serially sectioned with a cryostat in the horizontal plane at a thickness of 20 lm. The morphology of migrating SPN in reelin electroporated embryos was studied using retrograde DiI labeling (Yip et al, 2007). reelin Electroporated embryos at S28 were fixed in 4% paraformaldehyde.…”
Section: Retrograde Labeling Of Spnmentioning
confidence: 99%